2018
DOI: 10.1590/s1980-657420180003e0055-18
|View full text |Cite
|
Sign up to set email alerts
|

Are regional differences in basketball already established in under-18 games?

Abstract: To identify regional differences in basketball games for under-age categories, this study analyzed game-related statistics of four continental championships for under-18 (U18) men. Methods: A total of 149 games from each continental championship for U18 men held in 2016 were analyzed. A one-way analysis of variance followed by a Bonferroni post hoc test was performed to assess differences in game-related statistics between the continents (Europe, Africa, America, Asia). A discriminant analysis was performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…This assumption is also supported by the fact that the number of assists, which has been considered as an indicator of a well-organized offense [16,27,28], in the European championship, was relatively high among the four continental championships (second to the Asian championship). These performance profiles were consistent with previously reported findings in continental championships for senior [2] and junior [3] men. It is suggested that the basic performance profiles of European basketball are common to both sexes.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This assumption is also supported by the fact that the number of assists, which has been considered as an indicator of a well-organized offense [16,27,28], in the European championship, was relatively high among the four continental championships (second to the Asian championship). These performance profiles were consistent with previously reported findings in continental championships for senior [2] and junior [3] men. It is suggested that the basic performance profiles of European basketball are common to both sexes.…”
Section: Discussionsupporting
confidence: 92%
“…Cohen’s d was calculated as an effect size and interpreted as follows: d = 0.20 to 0.49, small effect; d = 0.50 to 0.79, medium effect; d ≥ 0.80, large effect [25]. To identify game-related statistics that discriminate between the continents, a discriminant analysis was performed using R code ‘candis’ and ‘geneig’, which have been used in previous studies [3,6,11,26]. An absolute value of a structural coefficient (SC) greater than or equal to 0.30 was considered relevant for the discrimination between the continents [2,3].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations